The impact of border control policy on tourists' behaviors in Taiwan during the COVID-19 pandemic. (December 2022) - Chen, Chiang-Ming; Jih, Chia-Yu; Lin, Yu-Chen; Hung, Wei-Hsi
Abstract: In response to the global pandemic of the COVID-19 outbreak, Taiwan barred foreign nationals from entering into Taiwan starting from March 19th, 2020. This study aims to explore the impact of lockdown policy on the length of stay, tourism expenditure, tourist satisfaction and revisit intention based on a sample of 3987 inbound visitors collected from the 2020 Annual Survey Report on Visitor Expenditures and Trends, published by the Taiwan Tourism Bureau. The empirical results indicate that: (1) the border control policy increases the length of stay of around 33.4719 nights; (2) a drop of the total expenditure, F&B expenditure, transportation expenditure, entertainment expenditure, and shopping expenditure but an increase of accommodation expenditure is found; (3) the border control policy seems to reduce the level of tourist satisfaction but does not affect revisit intention.